PERANCANGAN MEDIA PROMOSI KOMUNITAS SENI KUFLET PADANG PANJANG - Akbar, Rizka Lovani; Sudiani, Yoni; Rahman, Fadlul; Juned, Sulaiman (Melayu Arts and Performance Journal, 2025)
The Kuflet Art Community is an art community focused onliterature and theater, offering a platform for artists toexpress their creativity as part of a group with sharedinterests. An effective promotional media concept isnecessary to address the challenges in reaching a wideraudience and strengthening the community's image, which ishighly dedicated to literacy. The target audience for thisdesign includes artists, art practitioners, and anyoneinvolved in the arts in Padang Panjang City. The methodsused in designing the promotional media include data collection through observation, interviews, andquestionnaires to understand the needs and characteristicsof the community. The design process is carried out byapplying design and animation principles relevant to theidentity of the Kuflet Art Community. The promotionalmedia is designed to provide information about thecommunity's programs, achievements, and relationships in an engaging and communicative manner. The design resultsinclude promotional media capable of convincing andinviting the target audience to join the Kuflet Art Communityand increasing public awareness of the community'sexistence. The media mix produced includes videos, posters, flyers, brochures, x-banners, stamps, business cards, lanyards, and various merchandise. This design is expectedto be the first step in a broader sustainable promotionalstrategy.